2007
DOI: 10.1038/nchembio.2007.32
|View full text |Cite
|
Sign up to set email alerts
|

Chemical genetic interrogation of natural variation uncovers a molecule that is glycoactivated

Abstract: Natural variation in human drug metabolism and target genes can cause pharmacogenetic or interindividual variation in drug sensitivity. We reasoned that natural pharmacogenetic variation in model organisms could be systematically exploited to facilitate the characterization of new small molecules. To test this, we subjected multiple Arabidopsis thaliana accessions to chemical genetic screens and discovered 12 accession-selective hit molecules. As a model for understanding this variation, we characterized natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 27 publications
0
78
0
Order By: Relevance
“…Chemical metabolism, uptake, transport, and target sites can vary between plant species, and consequently, many bioactive compounds can show species-or genotype-specific effects (37). We therefore examined the expression of ABA responsive genes after quinabactin applications to soybean, barley, and maize, diverse agricultural species that span the monocot-dicot split.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical metabolism, uptake, transport, and target sites can vary between plant species, and consequently, many bioactive compounds can show species-or genotype-specific effects (37). We therefore examined the expression of ABA responsive genes after quinabactin applications to soybean, barley, and maize, diverse agricultural species that span the monocot-dicot split.…”
Section: Resultsmentioning
confidence: 99%
“…ABA can normally activate a multiplicity of receptors in the wild-type context, and it is not yet clear if different receptors have different subfunctions. To date, selective ABA receptor activation has only been achieved using pyrabactin (1,29), which has strong agonist activity on PYR1 and PYL1 and activates a full complement of ABA-responsive gene transcription in imbibed seeds. The genetic removal of PYR1, but not PYL1, causes pyrabactin insensitivity during germination, which argues that the major cellular target of pyrabactin in seeds is PYR1 and that activating PYR1 is sufficient to activate seed ABA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the structural diversity of lignan glycosides strongly suggests that not all lignan UGTs belong to the UGT71 family since flavonoid UGTs form separate phylogenetic clades based on their various regio-specificities (Noguchi et al 2009). It was previously reported that Sesamum UGT71A9 participates in the glucosylation of an intrinsic furofuran lignan, sesaminol, while other UGT71 enzymes are involved in the glucosylation of the flavonoid/triterpene (Medicago UGT71G1), a growth inhibitor (Arabidopsis UGT71B2/HYR1), exogenous naphthols (Nicotiana UGT71A6,7,11), exogenous curcumin (Catharanthus UGT71E2), and endogenous phytohormone (Arabidopsis UGT71B6) (Kaminaga et al 2004;Noguchi et al 2008;Priest et al 2006;Taguchi et al 2003;Zhao et al 2007), so the target compounds of the UGT71 enzymes are evidently structurally diverse (Figure 3). In addition to these reports, the present results support the view that the UGT71 family enzymes possess promiscuous substrate specificity, and some of them have adapted to lignans.…”
Section: Glycosylation Activity Of Forsythia Ugtsmentioning
confidence: 99%